# |
ODE |
Mathematica |
Maple |
\[
{}2 y^{3} y^{\prime \prime }+y^{2} {y^{\prime }}^{2}-a \,x^{2}-b x -c = 0
\] |
✗ |
✗ |
|
\[
{}2 \left (y-a \right ) \left (y-b \right ) \left (y-c \right ) y^{\prime \prime }-\left (\left (y-a \right )^{2} \left (y-b \right ) \left (y-c \right )+\left (y-b \right ) \left (y-c \right )\right ) {y^{\prime }}^{2}+\left (y-a \right )^{2} \left (y-b \right )^{2} \left (y-c \right )^{2} \left (A_{0} +\frac {B_{0}}{\left (y-a \right )^{2}}+\frac {C_{1}}{\left (y-b \right )^{2}}+\frac {D_{0}}{\left (y-c \right )^{2}}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (4 y^{3}-a y-b \right ) y^{\prime \prime }-\left (6 y^{2}-\frac {a}{2}\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (4 y^{3}-a y-b \right ) \left (y^{\prime \prime }+f y^{\prime }\right )-\left (6 y^{2}-\frac {a}{2}\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}-2 x y \left (1-x \right ) \left (1-y\right ) \left (x -y\right ) y^{\prime \prime }+x \left (1-x \right ) \left (x -2 x y-2 y+3 y^{2}\right ) {y^{\prime }}^{2}+2 y \left (1-y\right ) \left (x^{2}+y-2 x y\right ) y^{\prime }-y^{2} \left (1-y\right )^{2}-f \left (y \left (y-1\right ) \left (y-x \right )\right )^{{3}/{2}} = 0
\] |
✗ |
✗ |
|
\[
{}2 x^{2} y \left (1-x \right )^{2} \left (1-y\right ) \left (x -y\right ) y^{\prime \prime }-x^{2} \left (1-x \right )^{2} \left (x -2 x y-2 y+3 y^{2}\right ) {y^{\prime }}^{2}-2 x y \left (1-x \right ) \left (1-y\right ) \left (x^{2}+y-2 x y\right ) y^{\prime }+b x \left (1-y\right )^{2} \left (x -y\right )^{2}-c \left (1-x \right ) y^{2} \left (x -y\right )^{2}-d x y^{2} \left (1-x \right ) \left (1-y\right )^{2}+a y^{2} \left (x -y\right )^{2} \left (1-y\right )^{2} = 0
\] |
✗ |
✗ |
|
\[
{}\left (y^{2}-1\right ) \left (a^{2} y^{2}-1\right ) y^{\prime \prime }+b \sqrt {\left (1-y^{2}\right ) \left (1-a^{2} y^{2}\right )}\, {y^{\prime }}^{2}+\left (1+a^{2}-2 a^{2} y^{2}\right ) y {y^{\prime }}^{2} = 0
\] |
✓ |
✗ |
|
\[
{}\left (c +2 b x +a \,x^{2}+y^{2}\right )^{2} y^{\prime \prime }+y d = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {y}\, y^{\prime \prime }-a = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {x^{2}+y^{2}}\, y^{\prime \prime }-a \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} = 0
\] |
✗ |
✓ |
|
\[
{}y \left (1-\ln \left (y\right )\right ) y^{\prime \prime }+\left (1+\ln \left (y\right )\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (b +a \sin \left (y\right )^{2}\right ) y^{\prime \prime }+a {y^{\prime }}^{2} \cos \left (y\right ) \sin \left (y\right )+A y \left (c +a \sin \left (y\right )^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}h \left (y\right ) y^{\prime \prime }+a h \left (y\right ) {y^{\prime }}^{2}+j \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}h \left (y\right ) y^{\prime \prime }-D\left (h \right )\left (y\right ) {y^{\prime }}^{2}-h \left (y\right )^{2} j \left (x , \frac {y^{\prime }}{h \left (y\right )}\right ) = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime } y^{\prime \prime }-x^{2} y y^{\prime }-x y^{2} = 0
\] |
✗ |
✗ |
|
\[
{}\left (x y^{\prime }-y\right ) y^{\prime \prime }+4 {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right ) y^{\prime \prime }-\left (1+{y^{\prime }}^{2}\right )^{2} = 0
\] |
✗ |
✓ |
|
\[
{}a \,x^{3} y^{\prime } y^{\prime \prime }+b y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}\left (\operatorname {f1} y^{\prime }+\operatorname {f2} y\right ) y^{\prime \prime }+\operatorname {f3} {y^{\prime }}^{2}+\operatorname {f4} \left (x \right ) y y^{\prime }+\operatorname {f5} \left (x \right ) y^{2} = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}+2 y^{\prime } y^{2}\right ) y^{\prime \prime }+2 y {y^{\prime }}^{3}+3 x y^{\prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}\left ({y^{\prime }}^{2}+y^{2}\right ) y^{\prime \prime }+y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}\left ({y^{\prime }}^{2}+a \left (x y^{\prime }-y\right )\right ) y^{\prime \prime }-b = 0
\] |
✓ |
✓ |
|
\[
{}\left (a \sqrt {1+{y^{\prime }}^{2}}-x y^{\prime }\right ) y^{\prime \prime }-{y^{\prime }}^{2}-1 = 0
\] |
✓ |
✓ |
|
\[
{}h \left (y^{\prime }\right ) y^{\prime \prime }+j \left (y\right ) y^{\prime }+f = 0
\] |
✗ |
✗ |
|
\[
{}{y^{\prime \prime }}^{2}-a y-b = 0
\] |
✓ |
✓ |
|
\[
{}a^{2} {y^{\prime \prime }}^{2}-2 a x y^{\prime \prime }+y^{\prime } = 0
\] |
✗ |
✓ |
|
\[
{}2 \left (x^{2}+1\right ) {y^{\prime \prime }}^{2}-x y^{\prime \prime } \left (x +4 y^{\prime }\right )+2 \left (x +y^{\prime }\right ) y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} {y^{\prime \prime }}^{2}-2 \left (3 x y^{\prime }+y\right ) y^{\prime \prime }+4 {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (2-9 x \right ) {y^{\prime \prime }}^{2}-6 x \left (1-6 x \right ) y^{\prime } y^{\prime \prime }+6 y^{\prime \prime } y-36 x {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}F_{1,1}\left (x \right ) {y^{\prime }}^{2}+\left (\left (F_{2,1}\left (x \right )+F_{1,2}\left (x \right )\right ) y^{\prime \prime }+y \left (F_{1,0}\left (x \right )+F_{0,1}\left (x \right )\right )\right ) y^{\prime }+F_{2,2}\left (x \right ) {y^{\prime \prime }}^{2}+y \left (F_{2,0}\left (x \right )+F_{0,2}\left (x \right )\right ) y^{\prime \prime }+F_{0,0}\left (x \right ) y^{2} = 0
\] |
✗ |
✗ |
|
\[
{}y {y^{\prime \prime }}^{2}-a \,{\mathrm e}^{2 x} = 0
\] |
✗ |
✗ |
|
\[
{}\left (a^{2} y^{2}-b^{2}\right ) {y^{\prime \prime }}^{2}-2 a^{2} y {y^{\prime }}^{2} y^{\prime \prime }+\left (a^{2} {y^{\prime }}^{2}-1\right ) {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{2}-x^{2} {y^{\prime }}^{2}+x^{2} y y^{\prime \prime }\right )^{2}-4 x y \left (x y^{\prime }-y\right )^{3} = 0
\] |
✓ |
✗ |
|
\[
{}\left (2 y^{\prime \prime } y-{y^{\prime }}^{2}\right )^{3}+32 y^{\prime \prime } \left (x y^{\prime \prime }-y^{\prime }\right )^{3} = 0
\] |
✓ |
✗ |
|
\[
{}\sqrt {a {y^{\prime \prime }}^{2}+b {y^{\prime }}^{2}}+c y y^{\prime \prime }+d {y^{\prime }}^{2} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }-a^{2} \left ({y^{\prime }}^{5}+2 {y^{\prime }}^{3}+y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime }+y^{\prime \prime } y-{y^{\prime }}^{2}+1 = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }-y^{\prime \prime } y+{y^{\prime }}^{2} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }+a y y^{\prime \prime } = 0
\] |
✗ |
✗ |
|
\[
{}x^{2} y^{\prime \prime \prime }+x y^{\prime \prime }+\left (2 x y-1\right ) y^{\prime }+y^{2}-f \left (x \right ) = 0
\] |
✗ |
✗ |
|
\[
{}x^{2} y^{\prime \prime \prime }+x \left (y-1\right ) y^{\prime \prime }+x {y^{\prime }}^{2}+\left (1-y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime \prime \prime }-y^{\prime } y^{\prime \prime }+y^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{2} y^{\prime \prime \prime }-18 y y^{\prime } y^{\prime \prime }+15 {y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{2} y^{\prime \prime \prime }-45 y y^{\prime } y^{\prime \prime }+40 {y^{\prime }}^{3} = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime } y^{\prime \prime \prime }-3 {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) y^{\prime \prime \prime }-3 y^{\prime } {y^{\prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+{y^{\prime }}^{2}\right ) y^{\prime \prime \prime }-\left (3 y^{\prime }+a \right ) {y^{\prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } y^{\prime \prime \prime }-a \sqrt {b^{2} {y^{\prime \prime }}^{2}+1} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{\prime \prime \prime \prime }-y^{\prime \prime } y^{\prime \prime \prime }+{y^{\prime }}^{3} y^{\prime \prime \prime } = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime } \left (f^{\prime \prime \prime }\left (x \right ) y^{\prime }+3 f^{\prime \prime }\left (x \right ) y^{\prime \prime }+3 f^{\prime }\left (x \right ) y^{\prime \prime \prime }+f \left (x \right ) y^{\prime \prime \prime \prime }\right )-y^{\prime \prime } f y^{\prime \prime \prime }+{y^{\prime }}^{3} \left (f^{\prime }\left (x \right ) y^{\prime }+f \left (x \right ) y^{\prime \prime }\right )+2 q \left (x \right ) {y^{\prime }}^{2} \sin \left (y\right )+\left (q \left (x \right ) y^{\prime \prime }-q^{\prime }\left (x \right ) y^{\prime }\right ) \cos \left (y\right ) = 0
\] |
✗ |
✗ |
|
\[
{}3 y^{\prime \prime } y^{\prime \prime \prime \prime }-5 {y^{\prime \prime \prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}9 {y^{\prime \prime }}^{2} y^{\left (5\right )}-45 y^{\prime \prime } y^{\prime \prime \prime } y^{\prime \prime \prime \prime }+40 y^{\prime \prime \prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-f \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime \prime } = f \left (y\right )
\] |
✗ |
✗ |
|
\[
{}\{x^{\prime }\left (t \right ) = a x \left (t \right ), y^{\prime }\left (t \right ) = b\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right ) = a y \left (t \right ), y^{\prime }\left (t \right ) = -a x \left (t \right )\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right ) = a y \left (t \right ), y^{\prime }\left (t \right ) = b x \left (t \right )\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right ) = a x \left (t \right )-y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )+a y \left (t \right )\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right ) = a x \left (t \right )+b y \left (t \right ), y^{\prime }\left (t \right ) = c x \left (t \right )+b y \left (t \right )\}
\] |
✓ |
✓ |
|
\[
{}\{a x^{\prime }\left (t \right )+b y^{\prime }\left (t \right ) = \alpha x \left (t \right )+\beta y \left (t \right ), b x^{\prime }\left (t \right )-a y^{\prime }\left (t \right ) = \beta x \left (t \right )-\alpha y \left (t \right )\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right ) = -y \left (t \right ), y^{\prime }\left (t \right ) = 2 x \left (t \right )+2 y \left (t \right )\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right )+3 x \left (t \right )+4 y \left (t \right ) = 0, y^{\prime }\left (t \right )+2 x \left (t \right )+5 y \left (t \right ) = 0\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right ) = -5 x \left (t \right )-2 y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )-7 y \left (t \right )\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right ) = a_{1} x \left (t \right )+b_{1} y \left (t \right )+c_{1}, y^{\prime }\left (t \right ) = a_{2} x \left (t \right )+b_{2} y \left (t \right )+c_{2}\}
\] |
✓ |
✓ |
|
\[
{}\{x^{\prime }\left (t \right )+2 y \left (t \right ) = 3 t, y^{\prime }\left (t \right )-2 x \left (t \right ) = 4\}
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+y \left (t \right )-t^{2}+6 t +1 = 0, y^{\prime }\left (t \right )-x \left (t \right ) = -3 t^{2}+3 t +1]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+3 x \left (t \right )-y \left (t \right ) = {\mathrm e}^{2 t}, y^{\prime }\left (t \right )+x \left (t \right )+5 y \left (t \right ) = {\mathrm e}^{t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+y^{\prime }\left (t \right )+2 x \left (t \right )+y \left (t \right ) = {\mathrm e}^{2 t}+t, x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-x \left (t \right )+3 y \left (t \right ) = {\mathrm e}^{t}-1]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-y \left (t \right ) = {\mathrm e}^{t}, 2 x^{\prime }\left (t \right )+y^{\prime }\left (t \right )+2 y \left (t \right ) = \cos \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[4 x^{\prime }\left (t \right )+9 y^{\prime }\left (t \right )+2 x \left (t \right )+31 y \left (t \right ) = {\mathrm e}^{t}, 3 x^{\prime }\left (t \right )+7 y^{\prime }\left (t \right )+x \left (t \right )+24 y \left (t \right ) = 3]
\] |
✓ |
✓ |
|
\[
{}[4 x^{\prime }\left (t \right )+9 y^{\prime }\left (t \right )+11 x \left (t \right )+31 y \left (t \right ) = {\mathrm e}^{t}, 3 x^{\prime }\left (t \right )+7 y^{\prime }\left (t \right )+8 x \left (t \right )+24 y \left (t \right ) = {\mathrm e}^{2 t}]
\] |
✓ |
✓ |
|
\[
{}[4 x^{\prime }\left (t \right )+9 y^{\prime }\left (t \right )+44 x \left (t \right )+49 y \left (t \right ) = t, 3 x^{\prime }\left (t \right )+7 y^{\prime }\left (t \right )+34 x \left (t \right )+38 y \left (t \right ) = {\mathrm e}^{t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right ) f \left (t \right )+y \left (t \right ) g \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right ) g \left (t \right )+y \left (t \right ) f \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+\left (a x \left (t \right )+b y \left (t \right )\right ) f \left (t \right ) = g \left (t \right ), y^{\prime }\left (t \right )+\left (c x \left (t \right )+d y \left (t \right )\right ) f \left (t \right ) = h \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right ) \cos \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right ) {\mathrm e}^{-\sin \left (t \right )}]
\] |
✓ |
✓ |
|
\[
{}[t x^{\prime }\left (t \right )+y \left (t \right ) = 0, t y^{\prime }\left (t \right )+x \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[t x^{\prime }\left (t \right )+2 x \left (t \right ) = t, t y^{\prime }\left (t \right )-\left (2+t \right ) x \left (t \right )-t y \left (t \right ) = -t]
\] |
✓ |
✓ |
|
\[
{}[t x^{\prime }\left (t \right )+2 x \left (t \right )-2 y \left (t \right ) = t, t y^{\prime }\left (t \right )+x \left (t \right )+5 y \left (t \right ) = t^{2}]
\] |
✓ |
✓ |
|
\[
{}[t^{2} \left (1-\sin \left (t \right )\right ) x^{\prime }\left (t \right ) = t \left (1-2 \sin \left (t \right )\right ) x \left (t \right )+t^{2} y \left (t \right ), t^{2} \left (1-\sin \left (t \right )\right ) y^{\prime }\left (t \right ) = \left (\cos \left (t \right ) t -\sin \left (t \right )\right ) x \left (t \right )+t \left (1-\cos \left (t \right ) t \right ) y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+y^{\prime }\left (t \right )+y \left (t \right ) = f \left (t \right ), x^{\prime \prime }\left (t \right )+y^{\prime \prime }\left (t \right )+y^{\prime }\left (t \right )+x \left (t \right )+y \left (t \right ) = g \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[2 x^{\prime }\left (t \right )+y^{\prime }\left (t \right )-3 x \left (t \right ) = 0, x^{\prime \prime }\left (t \right )+y^{\prime }\left (t \right )-2 y \left (t \right ) = {\mathrm e}^{2 t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )-y^{\prime }\left (t \right )+x \left (t \right ) = 2 t, x^{\prime \prime }\left (t \right )+y^{\prime }\left (t \right )-9 x \left (t \right )+3 y \left (t \right ) = \sin \left (2 t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )-x \left (t \right )+2 y \left (t \right ) = 0, x^{\prime \prime }\left (t \right )-2 y^{\prime }\left (t \right ) = 2 t -\cos \left (2 t \right )]
\] |
✓ |
✓ |
|
\[
{}[t x^{\prime }\left (t \right )-t y^{\prime }\left (t \right )-2 y \left (t \right ) = 0, t x^{\prime \prime }\left (t \right )+2 x^{\prime }\left (t \right )+t x \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right )+a y \left (t \right ) = 0, y^{\prime \prime }\left (t \right )-a^{2} y \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right ) = a x \left (t \right )+b y \left (t \right ), y^{\prime \prime }\left (t \right ) = c x \left (t \right )+d y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right ) = a_{1} x \left (t \right )+b_{1} y \left (t \right )+c_{1}, y^{\prime \prime }\left (t \right ) = a_{2} x \left (t \right )+b_{2} y \left (t \right )+c_{2}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right )+x \left (t \right )+y \left (t \right ) = -5, y^{\prime \prime }\left (t \right )-4 x \left (t \right )-3 y \left (t \right ) = -3]
\] |
✓ |
✓ |
|
\[
{}\left [x^{\prime \prime }\left (t \right ) = \left (3 \cos \left (a t +b \right )^{2}-1\right ) c^{2} x \left (t \right )+\frac {3 c^{2} y \left (t \right ) \sin \left (2 a t b \right )}{2}, y^{\prime \prime }\left (t \right ) = \left (3 \sin \left (a t +b \right )^{2}-1\right ) c^{2} y \left (t \right )+\frac {3 c^{2} x \left (t \right ) \sin \left (2 a t b \right )}{2}\right ]
\] |
✗ |
✗ |
|
\[
{}[x^{\prime \prime }\left (t \right )+6 x \left (t \right )+7 y \left (t \right ) = 0, y^{\prime \prime }\left (t \right )+3 x \left (t \right )+2 y \left (t \right ) = 2 t]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right )-a y^{\prime }\left (t \right )+b x \left (t \right ) = 0, y^{\prime \prime }\left (t \right )+a x^{\prime }\left (t \right )+b y \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[a_{1} x^{\prime \prime }\left (t \right )+b_{1} x^{\prime }\left (t \right )+c_{1} x \left (t \right )-A y^{\prime }\left (t \right ) = B \,{\mathrm e}^{i \omega t}, a_{2} y^{\prime \prime }\left (t \right )+b_{2} y^{\prime }\left (t \right )+c_{2} y \left (t \right )+A x^{\prime }\left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right )+a \left (x^{\prime }\left (t \right )-y^{\prime }\left (t \right )\right )+b_{1} x \left (t \right ) = c_{1} {\mathrm e}^{i \omega t}, y^{\prime \prime }\left (t \right )+a \left (y^{\prime }\left (t \right )-x^{\prime }\left (t \right )\right )+b_{2} y \left (t \right ) = c_{2} {\mathrm e}^{i \omega t}]
\] |
✓ |
✓ |
|
\[
{}[\operatorname {a11} x^{\prime \prime }\left (t \right )+\operatorname {b11} x^{\prime }\left (t \right )+\operatorname {c11} x \left (t \right )+\operatorname {a12} y^{\prime \prime }\left (t \right )+\operatorname {b12} y^{\prime }\left (t \right )+\operatorname {c12} y \left (t \right ) = 0, \operatorname {a21} x^{\prime \prime }\left (t \right )+\operatorname {b21} x^{\prime }\left (t \right )+\operatorname {c21} x \left (t \right )+\operatorname {a22} y^{\prime \prime }\left (t \right )+\operatorname {b22} y^{\prime }\left (t \right )+\operatorname {c22} y \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right )-2 x^{\prime }\left (t \right )-y^{\prime }\left (t \right )+y \left (t \right ) = 0, y^{\prime \prime \prime }\left (t \right )-y^{\prime \prime }\left (t \right )+2 x^{\prime }\left (t \right )-x \left (t \right ) = t]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right )+y^{\prime \prime }\left (t \right )+y^{\prime }\left (t \right ) = \sinh \left (2 t \right ), 2 x^{\prime \prime }\left (t \right )+y^{\prime \prime }\left (t \right ) = 2 t]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right )-x^{\prime }\left (t \right )+y^{\prime }\left (t \right ) = 0, x^{\prime \prime }\left (t \right )+y^{\prime \prime }\left (t \right )-x \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 2 x \left (t \right ), y^{\prime }\left (t \right ) = 3 x \left (t \right )-2 y \left (t \right ), z^{\prime }\left (t \right ) = 2 y \left (t \right )+3 z \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = 4 x \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )-2 y \left (t \right ), z^{\prime }\left (t \right ) = x \left (t \right )-4 y \left (t \right )+z \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right )-z \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )+y \left (t \right ), z^{\prime }\left (t \right ) = x \left (t \right )+z \left (t \right )]
\] |
✓ |
✓ |
|